Решите уравнение, прошу: (7х+1)(х-3)+20(х-1)(х+1)=3(3х-2)²+13

Решите уравнение, прошу: (7х+1)(х-3)+20(х-1)(х+1)=3(3х-2)²+13
Гость
Ответ(ы) на вопрос:
Гость
(a-b)²=a²-2ab+b² a²-b²=(a-b)(a+b) (7х+1)(х-3)+20(х-1)(х+1)=3(3х-2)²+13 (7х+1)(х-3)=7x²+x-21x-3=7x²-20x-3 (х-1)(х+1)=x²-1²=x²-1 (3х-2)²=3²x²-2*3x*2+2²=9x²-12x+4 (7х+1)(х-3)+20(х-1)(х+1)=3(3х-2)²+13 (7x²-20x-3)+20(x²-1)=3(9x²-12x+4)+13 7x²-20x-3+20x²-20=27x²-36x+12+13 7x²+20x²-27x²-20x+36x=12+13+3+20 16x=48 x=48÷16 x=3
Гость
Решение в скане Красиво. Спасибо за задачку.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы